Determining the Concept and Structure of Forensic Characteristics of Murders Committed in Connection with Domestic Violence (Law and Safety, 2020)
Ukraine continues to work actively to combat domestic violence. The most serious crime that can be committed in this direction is murder, which was preceded by all kinds of domestic violence. There are innovations in criminal law aimed at protecting people from domestic violence. However, murders committed in connection with its use are not legally separated into a certain group of murders and have no qualifying features. In particular, there is no forensic characteristic of murders committed in connection with domestic violence.The purpose of the work is to define the concept, forensic characteristics of murders committed in connection with domestic violence, and its constituent elements. The general to partial method is used to establish the elements of the forensic characteristics of murders committed in connection with domestic violence. The forensic characteristics of all intentional homicides were taken as the basis. Besides, the author has carried out analysis of the main elements that assisted to distinguish these murders into a separate group, their mandatory features, namely family ties, the place of murder’s commission and the systematic use of domestic violence.Based on the analysis of scientific research, we have identified the concept of forensic characteristics of murders committed in connection with domestic violence, the constituent elements of the structure of forensic characteristics of such murders and their role in the investigation of criminal offenses.
Keywords: forensic characteristics; elements; a murder; domestic violence; structure